2016
DOI: 10.1002/ajim.22569
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive analysis and comparison of two French occupational exposure databases: COLCHIC and SCOLA

Abstract: COLCHIC and SCOLA represent a considerable source of information, but result from different purposes (prevention, regulatory). Potential differences due to strategies should evaluated when interpreting data from these databases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Companies with a common medical supervision and with available metrological data on the exposure of employees to free silica were selected. For this, the COLCHIC database from the “Institut National de Recherche et Sécurité” (15, 16) and files from the “Caisse d'Assurance Retraite et de la Santé au Travail” and the “Laboratoire Interrégional de Chimie de l'Ouest” were used. Free-silica exposure was ranked as “low,” “moderate” or “high” in respect to CS exposure and according to the metrological data from the COLCHIC database: sampling used an air sampler that captures the respirable (alveolar) fraction of airborne particles (European Standard CN 481).…”
Section: Methodsmentioning
confidence: 99%
“…Companies with a common medical supervision and with available metrological data on the exposure of employees to free silica were selected. For this, the COLCHIC database from the “Institut National de Recherche et Sécurité” (15, 16) and files from the “Caisse d'Assurance Retraite et de la Santé au Travail” and the “Laboratoire Interrégional de Chimie de l'Ouest” were used. Free-silica exposure was ranked as “low,” “moderate” or “high” in respect to CS exposure and according to the metrological data from the COLCHIC database: sampling used an air sampler that captures the respirable (alveolar) fraction of airborne particles (European Standard CN 481).…”
Section: Methodsmentioning
confidence: 99%
“…A comparison of the French COLCHIC database containing inspection measurements with the SCOLA database containing measurements focused on prevention found that the median concentrations were over three times higher in COLCHIC than in SCOLA; however, the differences were attenuated once sampling duration was taken into account [54]. In contrast, comparisons of the COLCHIC and US OSHA IMIS inspection databases provided similar multi-industry portraits of formaldehyde exposure despite a potential for very different occupational settings [7].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, all atmospheric concentration measurements conducted by the interregional chemical laboratories of the French regional health insurance funds or by INRS laboratories as part of preventive programmes, prospection, or support for epidemiological studies, are archived in the COLCHIC database [10]. The COLCHIC and SCOLA databases share a common technical structure and comparisons of exposure levels between the two databases are therefore possible [11]. In addition, as the data are derived from different sources, there are no double-entries in the two databases.…”
Section: Methodsmentioning
confidence: 99%